Typhoidal Tularemia: 2 Familial Cases - J. F. Faucher; C. Chirouze; C. Coutris; C. Fery-Blanco; M. Maurin; B. Hoen (Case Reports in Infectious Diseases)
Eastern France was not known as a region endemic for tularemia until year 2006. We report on 2 cases of typhoidal tularemia in Eastern France, a 43-year-old hospitalized woman and her husband. Diagnosis was established after fever clearance on serodiagnosis criteria. The source of infection is unclear. As persons in the same family may likely be exposed to a common zoonotic source of infection, tularemia should be considered in the etiologies of familial fever epidemics.